Empowering Human Resources in Village Projects with Cash Intensive in Tanjungharja Village - Mirajhusnita, Isradias; Mustaqim, Mustaqim; Nurwildani, Fajar (ASEAN Journal of Empowering Community, 2022)
Human resource empowerment programs have been carried out by the government. This is in line with Indonesia's development goal of building the whole Indonesian people, so development must be a social change that does not only occur in the standard of life of the community but also in the role of the elements in it. Development places man as the subject of development. Community empowerment in the conditions of the COVID-19 pandemic in a cash-intensive program. Poverty is a social welfare development problem related to various other areas of development characterized by unemployment, underdevelopment, and helplessness. Therefore, poverty, especially suffered by the poor, is a national staple problem whose mitigation cannot be delayed any longer and must be a top priority in the implementation of social welfare development.  The handling of the poor is not easy, because the poor have experienced a long-lasting problem of poverty. The poor experience limitations in terms of education, skills, business facilities and business capital. Plus the conditions in the Coronavirus Desease 2019 (COVID-19) pandemic. The government continues to strive to maintain the social and economic life of the community with the Cash Intensive program. Tanjungharja Village consists of 4 villages, 7 community units (RW) and 24 neighboring pillars (RT).